Interregional Inequality and Federal Expenditures and Transfers in Russia - Alexander Torbenko (European Regional Science Association (ERSA), 2014)
The paper considers the influence of federal government expenditures and transfers on interregional convergence in gross regional product (GRP) per capita and wages in Russia over 2005?2011. Such an influence is not found. The federal government's policy was reactive and was not focused on decreasing interregional inequality during this period. Wages growth depended more on GRP per capita growth than on federal govern- ment spendings and transfers per capita growth. The dependence between GRP per capita growth and federal government spendings and transfers per capita growth was very weak. Moreover, the paper shows that in this period inequality of Russian regions in GRP per capita and wages was diminishing. In the given period in Russian regions there existed un- conditional beta-convergence, poor regions grew faster than rich ones. This result confirms the prediction of neoclassical theory of regional growth and challenges a new economic geography prediction. Comparing our results to the results of previous research the process of interregional convergence in Russia can be seen. In the 1990s, with the state pressure having been eliminated, the differentiation between Russian regions began, while in the 2000s a natural process of (conditional or unconditional) convergence started.
Keywords: C13; R11; R12; R58; 330; convergence; federal expenditures and transfers; wages; Russia; regions; gross regional product